Very high brightness and power LCLS‐II hard X‐ray pulses. (4th April 2019) - Halavanau, Aliaksei; Decker, Franz-Josef; Emma, Claudio; Sheppard, Jackson; Pellegrini, Claudio
Abstract : High peak power and high brightness hard X‐ray generation achievable in the double‐bunch LCLS‐II operation is reported. Abstract : The feasibility of generating X‐ray pulses in the 4–8 keV fundamental photon energy range with 0.65 TW peak power, 15 fs pulse duration and 9 × 10 −5 bandwidth using the LCLS‐II copper linac and hard X‐ray (HXR) undulator is shown. In addition, third‐harmonic pulses with 8–12 GW peak power and narrow bandwidth are also generated. High‐power and small‐bandwidth X‐rays are obtained using two electron bunches separated by about 1 ns, one to generate a high‐power seed signal, the other to amplify it through the process of the HXR undulator tapering. The bunch delay is compensated by delaying the seed pulse with a four‐crystal monochromator. The high‐power seed leads to higher output power and better spectral properties, with more than 94% of the X‐ray power within the near‐transform‐limited bandwidth. Some of the experiments made possible by X‐ray pulses with these characteristics are discussed, such as single‐particle imaging and high‐field physics.